Customer Experience And Satisfaction: The Impact Of Augmented Reality In Online Shopping - Michelle Alicia Lynch; William Leo Walangitan; Aaron Kennedy; Hari Setiabudi Husni (International Journal Multidisciplinary Science, 2025)
The rapid growth of e-commerce presents challenges related to limited product visualization and customer engagement, which refers to the degree to which customers feel actively involved in the online shopping experience. Augmented Reality (AR) technology has the potential to offer an innovative solution by providing an immersive shopping experience that makes customers feel as if they are interacting directly with products through virtual simulations. This research aims to explore how AR can provide a deeper customer experience and satisfaction in online shopping, such as realistically visualizing products before purchase, with an example application of the "try before you buy" feature (virtual try-on) in online shopping applications. The approach to be used in this research is quantitative, with data collection from AR users in online shopping activities. The research results are not yet obtained and are in the conceptual stage, it is hoped that this research can reveal opportunities for the use of AR as a strategic technology that can support more attractive and efficient online shopping activities. Recommendations that can be made for the future include the need for valid data collection and analysis, and the use of appropriate methodologies to explore the effectiveness of AR in greater depth. Future research topics can explore the influence of AR on customer preferences based on specific types of products or categories in online shopping.